2021
DOI: 10.17691/stm2021.13.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Apoptotic Markers Bcl-2 and Bax in the Vascular Wall

Abstract: The aim of the study was to assess the levels of Всl-2 and Bax proteins in the vascular wall and their correlation with serum cholesterol in patients with stage III-IV atherosclerosis obliterans of lower limb arteries.Materials and Methods. The study included 32 patients with stage III-IV atherosclerosis obliterans of the lower limb. Samples of intraoperative material (all three layers of the vascular wall) including an atherosclerotic plaque (AP) were taken during primary open surgery on major leg arteries. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…On the contrary, the circRNA inhibited RAFLS apoptotic rate. The Bcl-2 protein family is important to the apoptosis system and regulates the mitochondrial membrane permeability, including proapoptotic protein such as BAX and anti-apoptotic protein such as BCL-2 [ 18 ]. Herein, the study detected BAX and BCL-2 expression after circ_0002984 knockdown or overexpression and found that circ_0002984 increased BCL-2 protein production and decreased BAX protein expression, which supported the anti-apoptotic role of circ_0002984 in RAFLSs.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the circRNA inhibited RAFLS apoptotic rate. The Bcl-2 protein family is important to the apoptosis system and regulates the mitochondrial membrane permeability, including proapoptotic protein such as BAX and anti-apoptotic protein such as BCL-2 [ 18 ]. Herein, the study detected BAX and BCL-2 expression after circ_0002984 knockdown or overexpression and found that circ_0002984 increased BCL-2 protein production and decreased BAX protein expression, which supported the anti-apoptotic role of circ_0002984 in RAFLSs.…”
Section: Discussionmentioning
confidence: 99%